Strategi Pemberdayaan Pembangunan Pendidikan: Studi Kasus Distrik Beoga Barat Kabupaten Puncak - Kalabetme, Miren; Lefaan, Avelinus (JURNAL EKOLOGI BIROKRASI, 2023)
This article aims to analyze the implementation of the tasks and functions of educational empowerment, analyze the role of the government in educational empowerment, and analyze the strategies of educational empowerment in Beoga Village, West Beoga District, Puncak Regency. Research method: Case study method. This thesis concludes several things as follows: The tasks and functions of educational empowerment in West Beoga District can be said to be not going well, especially in implementing the tasks and functions of education as an actor in socializing the nation's socio-cultural ideology and values, preparing the workforce to reduce poverty, ignorance and promote social change, and equal distribution of income and opportunities, caused by the security conditions (conflict areas) that resulted in the absence of learning activities in schools, in addition to the absence of teachers who were displaced and afraid of the conflict, as well as the reluctance of students to go to school due to the conflict that occurred. The role of educational empowerment as community servants, facilitators and provision of funds is not working well in North Beoga district, this can be seen from the lack of development of existing educational facilities and infrastructure such as local classes, reading books, curriculum, teaching aids and the inadequate quality of teachers. This role is also not optimal due to the lack of local government budget support for the education sector. The educational empowerment strategy, especially in improving the quality of teachers and students, is not working well. This condition is characterized by the lack of development of teachers' competence and professionalism through education and training, technical guidance and strengthening of other competencies, thus affecting the quality of education services in West Beoga District.